1989
DOI: 10.1113/expphysiol.1989.sp003257
|View full text |Cite
|
Sign up to set email alerts
|

Drinking and Vasopressin Release Following Central Injections of Angiotensin Ii in Minipigs

Abstract: SUMMARYAngiotensin II (AII; 300 ng) injected into the lateral cerebral ventricle produced significant drinking responses and also stimulated release of lysine vasopressin (LVP) in conscious, water replete, unrestrained minipigs. Plasma LVP concentration, measured by a specific radioimmunoassay, was decreased by drinking. At the end of the experiment the level was inversely proportional to the volume of water drunk in response to the AII, and not to changes in plasma osmolality. These findings suggest that All-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…The role of oropharyngeal receptors in attenuating thirst has been extensively studied in both human [11,17,23,24,25,26] and animal models [27,28,29,30]. Figaro and Mack [11] showed that oropharyngeal receptors played an immediate role in inhibiting thirst, and thus, fluid intake, without influencing plasma osmolality when fluid was extracted immediately from the stomach after consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The role of oropharyngeal receptors in attenuating thirst has been extensively studied in both human [11,17,23,24,25,26] and animal models [27,28,29,30]. Figaro and Mack [11] showed that oropharyngeal receptors played an immediate role in inhibiting thirst, and thus, fluid intake, without influencing plasma osmolality when fluid was extracted immediately from the stomach after consumption.…”
Section: Discussionmentioning
confidence: 99%